Characteristics and Demographics of Patients Requiring Emergent Air Medical - Anna Van Tuyl; Mark Quilon; Trevor Dudley; Olivia Grant; Neha Rao; Paul Barbara; David S. Kugler; Kaitlin C. McLoone-Cepin; Josh Greenstein; Barry Hahn (Emergency Medicine International)
Background. As integrated health systems become more common, interfacility patient transfers will increase and air transport programs will be prioritized. Understanding characteristics of patients triaged to air medical transport will assist with resource allocation and needs assessment. The objective of this study was to investigate the demographics and clinical characteristics of patients that presented to the emergency department (ED) and subsequently required emergent air medical interfacility transport. Methods. This was a retrospective, multicenter study conducted at eight hospitals within Northwell Health, the largest academic health system in New York state. The study was conducted between December 1, 2014, and July 31, 2020, and included patients who presented to an ED and subsequently required emergent air medical interfacility transport. Results. Overall, the median age was 37 years (IQR 4–66), and 231 (54%) subjects were males. The majority of subjects (59%) had no reported comorbidities, arrived by ambulance (52%), and were emergency severity index triage 2 (48%). Frequent indications for transfer were nontraumatic neurologic (37%), pulmonary or respiratory (13%), trauma (12%), and cardiovascular (12%). Most patients were not ventilated before transport (71%). The median time to call for transport at the sending institution was 2:42 hours (IQR 1:14–6:54), and the median length of stay was 4:12 (IQR 2:31–8:48). Most patients were subsequently admitted (96%) at the receiving institution to an intensive care unit (72%). Conclusions. This study describes patients’ demographic and clinical characteristics who required emergent air medical transport. Helicopter transport is costly, and data from these patients may further help our understanding of who is transported by air and how important air transport is to the health system.